Additive manufacturing of WC-13%Co by selective electron beam melting: Achievements and challenges. (November 2019) - Konyashin, I.; Hinners, H.; Ries, B.; Kirchner, A.; Klöden, B.; Kieback, B.; Nilen, R.W.N.; Sidorenko, D.
Abstract: Additive manufacturing is a powerful tool for rapid prototyping and fabricating metal articles having a complicated geometry. This method is known to be used almost solely for the manufacture of articles consisting of pure metals and alloys. In the present work the possibility of obtaining dense carbide articles by a single-step process of additive manufacturing based on selective electron beam melting was evaluated. A new technology for fabricating cemented carbide granules suitable for selective electron beam melting was developed. It includes conventional granulating WC-Co powders followed by solid-state pre-sintering and preliminary screening of the granules. After that their liquid-phase sintering and final screening are carried out to obtain a desired fraction needed for the additive manufacturing process. Results of experiments on selective electron beam melting at different scan rates and current values indicated that it was possible to obtain non-porous carbide articles of complex geometry from WC-Co granules initially containing 13 wt% Co. The selective electron beam melting process led to the evaporation of some liquid Co and very intense local WC grain growth resulting in peculiar microstructures of the cemented carbide articles comprising layers with medium-coarse and abnormally large WC grains. A near-surface layer of the cemented carbide articles obtained by additive manufacturing is characterized by a high roughness comparable with the mean size of the original WC-Co granules. Highlights: Non-porous carbide articles of complex geometry were made by additive manufacturing. Novel technology for fabricating dense cemented carbide granules was developed. The granules are suitable for additive manufacturing of the cemented carbide articles. Intense local WC grain growth resulting in peculiar microstructures was established. Near-surface layer of the cemented carbide articles is characterized by high roughness.